P.147 Evaluation of Arterial Spin Labeling (ASL) perfusion imaging in poorly- defined focal epilepsy in children. (June 2022) - Lam, J; Tomaszewski, P; Gilbert, G; Moreau, JT; Guiot, M; Farmer, J; Atkinson, J; Saint-Martin, C; Wintermark, P; Bernhardt, B; Baillet, S; Dudley, RW
Abstract : Background: Poorly-defined cases (PDCs) of focal epilepsy are cases with no/subtle MRI abnormalities or have abnormalities extending beyond the lesion visible on MRI. Here, we evaluated the utility of Arterial Spin Labeling (ASL) MRI perfusion in PDCs of pediatric focal epilepsy. Methods: ASL MRI was obtained in 25 consecutive children presenting with poorly-defined focal epilepsy (20 MRI- positive, 5 MRI-negative). Qualitative visual inspection and quantitative analysis with asymmetry and Z-score maps were used to detect perfusion abnormalities. ASL results were compared to the hypothesized epileptogenic zone (EZ) derived from other clinical/imaging data and the resection zone in patients with Engel I/II outcome and >18 month follow-up. Results: Qualitative analysis revealed perfusion abnormalities in 17/25 total cases (68%), 17/20 MRI-positive cases (85%) and none of the MRI-negative cases. Quantitative analysis confirmed all cases with abnormalities on qualitative analysis, but found 1 additional true-positive and 4 false-positives. Concordance with the surgically-proven EZ was found in 10/11 cases qualitatively (sensitivity=91%, specificity=50%), and 11/11 cases quantitatively (sensitivity=100%, specificity=23%). Conclusions: ASL perfusion may support the hypothesized EZ, but has limited localization benefit in MRI-negative cases. Nevertheless, owing to its non-invasiveness and ease of acquisition, ASL could be a useful addition to the pre-surgical MRI evaluation of pediatric focal epilepsy.